ASXL1 mutations are associated with distinct epigenomic alterations that lead to sensitivity to venetoclax and azacytidine - Rahmani, NE; Ramachandra, N; Sahu, S; Gitego, N; Lopez, A; Pradhan, K; Bhagat, TD; Gordon-Mitchell, S; Pena, BR; Kazemi, M; Rao, K; Giricz, O; et al. (Springer Nature, 2021)
The BCL2-inhibitor, Venetoclax (VEN), has shown significant anti-leukemic efficacy in combination with the DNMT-inhibitor, Azacytidine (AZA). To explore the mechanisms underlying the selective sensitivity of mutant leukemia cells to VEN and AZA, we used cell-based isogenic models containing a common leukemia-associated mutation in the epigenetic regulator ASXL1. KBM5 cells with CRISPR/Cas9-mediated correction of the ASXL1G710X mutation showed reduced leukemic growth, increased myeloid differentiation, and decreased HOXA and BCL2 gene expression in vitro compared to uncorrected KBM5 cells. Increased expression of the anti-apoptotic gene, BCL2, was also observed in bone marrow CD34+ cells from ASXL1 mutant MDS patients compared to CD34+ cells from wild-type MDS cases. ATAC-sequencing demonstrated open chromatin at the BCL2 promoter in the ASXL1 mutant KBM5 cells. BH3 profiling demonstrated increased dependence of mutant cells on BCL2. Upon treatment with VEN, mutant cells demonstrated increased growth inhibition. In addition, genome-wide methylome analysis of primary MDS samples and isogenic cell lines demonstrated increased gene-body methylation in ASXL1 mutant cells, with consequently increased sensitivity to AZA. These data mechanistically link the common leukemia-associated mutation ASXL1 to enhanced sensitivity to VEN and AZA via epigenetic upregulation of BCL2 expression and widespread alterations in DNA methylation.